2023
DOI: 10.1177/18344909231167533
|View full text |Cite
|
Sign up to set email alerts
|

Growth mindset predicts teachers’ life satisfaction when they are challenged to innovate their teaching

Abstract: Teaching innovations can improve the quality of education and facilitate adaptation to environmental shifts caused by global shocks such as the COVID pandemic. However, the pressure to innovate and change may also cause erosion of teachers’ life satisfaction, especially when job resources are insufficient and support for the changes is inadequate, or when teachers lack confidence in mastering new teaching technology. In the present research, we showed that compared to those who did not, teachers who presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…To conclude, based on this review, it seems that both in-service and pre-service teachers mostly hold a growth mindset when measured with self-reports (e.g., Jones et al, 2012;Gutshall, 2013;Patterson et al, 2016;Makkonen et al, 2019;Snyder et al, 2021;Meierdirk and Fleischer, 2022;Graham et al, 2023;Lee et al, 2023). Furthermore, most studies on the manifestation of teachers' mindsets and the connection between teachers' mindsets and growth-oriented practices, on the one hand, and students' mindsets and learning, on the other, reported at least some connection between the former and the latter.…”
Section: A Brief Summary Of the Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…To conclude, based on this review, it seems that both in-service and pre-service teachers mostly hold a growth mindset when measured with self-reports (e.g., Jones et al, 2012;Gutshall, 2013;Patterson et al, 2016;Makkonen et al, 2019;Snyder et al, 2021;Meierdirk and Fleischer, 2022;Graham et al, 2023;Lee et al, 2023). Furthermore, most studies on the manifestation of teachers' mindsets and the connection between teachers' mindsets and growth-oriented practices, on the one hand, and students' mindsets and learning, on the other, reported at least some connection between the former and the latter.…”
Section: A Brief Summary Of the Resultsmentioning
confidence: 82%
“…By contrast, teachers with a fixed mindset avoided helpseeking because of a fear of failure or from the desire to cope independently (Inbar-Furst and Gumpel, 2015). Similarly, Lee et al (2023) found that teachers' growth mindsets were positively associated with perceptions of a new "positive education program" (study 1) and with teachers' self-efficacy regarding online teaching (study 2). Teachers' growth mindsets have also been linked to a more receptive attitude toward curriculum reform (Huang, 2023).…”
Section: Pedagogical Thinking and Practicementioning
confidence: 90%
See 1 more Smart Citation
“…Related to this question is the consistently small negative correlation between the growth mindset and fixed mindset in Chinese samples (e.g., Lee et al, 2023). This is an anomaly because this empirical dissociation of the growth mindset from the fixed mindset may seem logically impossible.…”
Section: The Ambivalent Mindsetmentioning
confidence: 99%
“…Thus, we should expect a sizeable negative correlation between endorsement of the two mindsets. However, in research conducted in Hong Kong, the negative correlations of the two mindsets were typically small (see Lee et al, 2023). For example, between 2017 and 2019, we collected mindset data from 594 teachers (67.1% female; mean age = 31.91 years, SD = 17.76 years) from 5 primary schools and 3 secondary schools in Hong Kong.…”
Section: The Ambivalent Mindsetmentioning
confidence: 99%